Effects of drop-height and surface instability on jump performance and knee kinematics - Lesinski, Melanie; Prieske, Olaf; Beurskens, Rainer; Behm, David; Granacher, Urs (International journal of sports medicine, 2018)
The purpose of this study was to examine the combined effects of drop-height and surface condition on drop jump (DJ) performance and knee joint kinematics. DJ performance, sagittal and frontal plane knee joint kinematics were measured in jump experienced young male and female adults during DJs on stable, unstable and highly unstable surfaces using different drop-heights (20, 40, 60 cm). Findings revealed impaired DJ performance (Δ5-16%; p<0.05; 1.43≤d≤2.82), reduced knee valgus motion (Δ33-52%; p<0.001; 2.70≤d≤3.59), and larger maximum knee flexion angles (Δ13-19%; p<0.01; 1.74≤d≤1.75) when using higher (60 cm) compared to lower drop-heights (≤40 cm). Further, lower knee flexion angles and velocity were found (Δ8-16%; p<0.01; 1.49≤d≤2.38) with increasing surface instability. When performing DJs from high (60 cm) compared to moderate drop-heights (40 cm) on highly unstable surfaces, higher knee flexion velocity and maximum knee valgus angles were found (Δ15-19%; p<0.01; 1.50≤d≤1.53). No significant main and/or interaction effects were observed for the factor sex. In conclusion, knee motion strategies were modified by the factors ‘drop-height’ and/or ‘surface instability’. The combination of high drop-heights (>40 cm) together with highly unstable surfaces should be used cautiously during plyometrics because this may increase the risk of injury due to higher knee valgus stress.
Published online: 9.11.2017
Gesehen am 20.04.2020